2010
DOI: 10.1111/j.1540-6237.2010.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Government Redistribution Across Countries: The Problem of Second‐Order Effects*

Abstract: Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz gewährten Nutzungsrechte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 19 publications
1
20
0
3
Order By: Relevance
“…Kim (2000b) showed that both the generosity and efficiency of the tax/transfer system could influence the level of pre‐tax‐transfer income inequality. There is also empirical work addressing these problems, using various measurement strategies (see e.g., Jesuit & Mahler, ). Budget incidence calculations can therefore be seen only as an approximation of the redistributive effects because of the assumption that agents behave similarly in situations with and without social transfers and social security.…”
Section: Methodsmentioning
confidence: 99%
“…Kim (2000b) showed that both the generosity and efficiency of the tax/transfer system could influence the level of pre‐tax‐transfer income inequality. There is also empirical work addressing these problems, using various measurement strategies (see e.g., Jesuit & Mahler, ). Budget incidence calculations can therefore be seen only as an approximation of the redistributive effects because of the assumption that agents behave similarly in situations with and without social transfers and social security.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been criticised on theoretical as well as methodological grounds (Bergh, ; Jesuit & Mahler, ). Two shortcomings were of particular concern for our study.…”
Section: The Universalism–targeting Debate and Child Benefit Designmentioning
confidence: 99%
“…Empirische Studien zur Umverteilungswirkung von Sozialstaaten leiden oft an einem Mangel an verfügbaren Daten. Dies hat sich kürzlich geändert durch die Arbeit von Mahler und Jesuit () und von Jesuit und Mahler (), welche LIS‐Daten verwendeten. Die Luxembourg Income Study (LIS) bietet Mikrodaten zu öffentlichen und privaten Einkommensquellen, die vergleichbar, detailliert und genau sind.…”
Section: Einführungunclassified